Forestry in Kerala: Yesterday, Today and Tomorrow - Sasidharan Nair, K.; Prabhu, Nagesh (Indian Forester, 1998)
Kerala is one of the most prosperous States of India. Its natural forests are very rich in biodiversity. It is the only State in India where the forestry sector is getting so much support from homestead forestry in meeting the timber and fuel wood requirement of the State, leading to sustainable management of biodiversity rich natural forests.